2001
DOI: 10.1177/019263650108562808
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Quality and Student Achievement: Recommendations for Principals

Abstract: Principals play major roles to ensure both teacher and teaching quality in classrooms. Understanding essential research findings on both teacher and teaching quality and their relation to student learning can help principals significantly improve student achievement.Improving teacher and teaching quality has become the "third wave" of education reform (Hirsch, Koppich, and Knapp 1998, 2). Increasingly, research confirms that capable teachers are the essential link between public aspirations for high-quality sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 3 publications
5
26
0
5
Order By: Relevance
“…A quality learning environment was a major concern of the interviewed school stakeholders in the facilitation of quality teaching and learning. These findings are supported by the previous literature by (Ainscow, 1991;Clark, Dyson, & Millward, 1995;Fraser, 1994Fraser, , 2002Kaplan & Owings, 2001;Killen, 2005;Lane & Walberg, 1987;Reynolds et al, 2003;Teddlie, Kirby, & Strinfield, 1989;Walker & Murphy, 1986) that argue that the teaching and learning environment, whether at the classroom level or at the whole school level, plays an important role in quality teaching and learning. The Jordanian school stakeholders mentioned social support as a fundamental element in the teaching and learning process.…”
Section: Quality Learning Environmentsupporting
confidence: 87%
See 2 more Smart Citations
“…A quality learning environment was a major concern of the interviewed school stakeholders in the facilitation of quality teaching and learning. These findings are supported by the previous literature by (Ainscow, 1991;Clark, Dyson, & Millward, 1995;Fraser, 1994Fraser, , 2002Kaplan & Owings, 2001;Killen, 2005;Lane & Walberg, 1987;Reynolds et al, 2003;Teddlie, Kirby, & Strinfield, 1989;Walker & Murphy, 1986) that argue that the teaching and learning environment, whether at the classroom level or at the whole school level, plays an important role in quality teaching and learning. The Jordanian school stakeholders mentioned social support as a fundamental element in the teaching and learning process.…”
Section: Quality Learning Environmentsupporting
confidence: 87%
“…In a quality learning environment that has regard for significance, the learning activities should be designed to interest and motivate males and females in a wide choice of potential career opportunities beyond the school context, and motivate students to recognize and enhance positive social developments in Jordan, to identify inequities that still remain, and to develop possible solutions (Ministry of Education, 2006a). These findings are consistent with the research by Biggs (1991); Borich (1999Borich ( , 2000; Bruner (1960); Christie (1985); Connell (1993); Darling-Hammond (1997); Dewey (1916); Newmann & Associates (1996); Glasser (1986); Kaplan & Owings (2001); Killen (2005); Meier (1995) that argue that a quality teaching process involves successful knowledge-gaining and the implementation of knowledge into the real life.…”
Section: Significancesupporting
confidence: 86%
See 1 more Smart Citation
“…Childs and McNicholl (2007) indicate that the teacher who lacks content knowledge resorts to constrained pedagogy and this was the case for Mr. Mulalo. Therefore, it can be concluded that the instructional strategies the teacher used did not promote comprehension of the abstract concepts which is a teaching difficulty because, according to Kaplan and Owings (2001), instructional strategies are also an important factor in student achievement.…”
Section: Empiricism and The Comprehension Of Abstract Conceptsmentioning
confidence: 99%
“…The teacher's knowledge which comprised content, context and students' prior knowledge revealed that it had deficiencies either in the knowledge itself or in the use of the knowledge during teaching. It is interesting to note that in terms of the description of Kaplan and Owings (2001) of teacher quality, Mr. Mulalo is a quality teacher because he is qualified and brought evidence of a preparation in the classroom. So, it cannot be surprising that Mr. Mulalo considered himself as such and expected the performance of students to be reciprocal and this was due to his perception that the topic was difficult to teach.…”
Section: Teacher Knowledgementioning
confidence: 99%